Group-based multimodal exercises integrated with cognitive-behavioural therapy improve disability, pain and quality of life of subjects with chronic neck pain: a randomized controlled trial with one-year follow-up. (June 2017) - Monticone, Marco; Ambrosini, Emilia; Rocca, Barbara; Cazzaniga, Daniele; Liquori, Valentina; Pedrocchi, Alessandra; Vernon, Howard
Objective: To evaluate the effect of a group-based multidisciplinary rehabilitation programme on disability, pain and quality of life in subjects with chronic neck pain. Design: Randomized controlled trial. Setting: Specialized rehabilitation centre. Subjects: A total of 170 patients (mean age of 53 years (13); 121 females). Interventions: The multidisciplinary group underwent a multidisciplinary rehabilitation programme combining multimodal exercises with psychologist-lead cognitive-behavioural therapy sessions. The general exercise group underwent general physiotherapy. Both groups followed group-based programmes once a week for ten weeks. Additionally, the multidisciplinary group met with the psychologist once a week for a 60-minute session. Main measures: The Neck Disability Index (primary outcome), the Tampa Scale for Kinesiophobia, the Pain Catastrophizing Scale, a pain numerical rating scale and the Short-Form Health Survey. The participants were evaluated before, after training and after 12 months. Results: A linear mixed model for repeated measures was used for each outcome measure. Significant effects ( p -value <0.001) were found over time and between groups for all outcome measures. After training, significant improvements were found for both groups for all outcome measures except kinesiophobia and catastrophizing, which did not change in the control group; however, the improvements were significantly greater for the multidisciplinary group. At 12-month follow-up a clinically meaningful between-group difference of 12.4 Neck Disability Index points was found for disability. Conclusions: A group-based multidisciplinary rehabilitation programme including cognitive-behavioural therapy was superior to group-based general physiotherapy in improving disability, pain and quality of life of subjects with chronic neck pain. The effects lasted for at least one year.